Proses Rekrutmen, Seleksi dan Penempatan Talenta Karyawan Terbaik di Lembaga Pendidikan - Hesti Kusumaningrum; Jihan Zalika Rachman; Mahesa Rangga Maulana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
An institution has main components in it, one of the important components is human resources. HR regulates all relations between workers in an institution with the aim of building good work performance and a good environment. The reality of inadequate human resources in Indonesia, especially in many institutions today, is something that must be addressed. Many factors cause the processes in accepting new employees to be less than optimal. This causes a decline in the performance of human resources in an institution, even though if it is implemented well the results will be maximum and can produce high performing and talented employees. The purpose of this writing is to provide structured processes for accepting new employees at an institution by following existing standards. Which can later be applied in everyday life and in the world of work for all facilitators and prospective new employees, so that they have a clear picture in the process of looking for qualified human resources that meet the Institution's standards. The author uses a qualitative approach with a library research method with references to several books and journal articles.